PERLINDUNGAN HAK CIPTA MELALUI REGULASI TOKOPEDIA DALAM PENJUALAN BUKU BAJAKAN SUPERNOVA - Chantry Dhityaenggarwangi; Dian Purnamasari (Reformasi Hukum Trisakti, 2021)
Books are objects protected by copyright under Article 40 of the Copyright Law. However, there are still parties who sell pirated books of Dee Lestari's Supernova on Tokopedia. Tokopedia is a marketplace platform, where sellers and buyers transact buying and selling online. Tokopedia has regulations governing what types of goods may not be traded. The formulation of the problem regarding the form of infringement in the sale of pirated books Supernova in the marketplace Tokopedia and copyright protection against the sale of pirated books Supernova through Regulation Tokopedia. The research method is normative legal research with secondary data and supported by primary data. The nature of the research is descriptive and drawing conclusions with deductive reasoning. The results of the research, discussion and conclusions of this article are that there is a form of violation of economic rights, namely unauthorized duplication and distribution without the permission of the creator or copyright holder in the sale of pirated Supernova books on Tokopedia. In addition, Tokopedia has regulations that provide copyright protection in the Tokopedia marketplace, but it has not been maximized so that there are still sales of Supernova pirated books on Tokopedia.